The requirements and solutions for a good video call user experience for elderly people - Laakkonen, Lauri (My University, 2022)
Socialising during Covid-19 pandemic has brought new challenges to tackle. Usage of technology and especially video calls are something which can bring a lot of new opportunities to handle the challenges. To be able to use video calls requires a targeted solution for elderly people and people who suffer from impairments brought on by ageing. Vooler is a custom made solution which is solving the issues that elderly people might face with more regular video call solutions. The thesis looks for answers about what current video calls are achieving and for what kind of users. There are also investigations about what kind of things have to be accounted for so elderly people can use video calls effectively and what sort of solutions can be used to handle difficulties that the users might face. Additionally accessibility has a big focus, since the probability of requiring some level of accessibility is high in elderly people. These are made into individual points and made as requirements in the thesis, so they can be used to evaluate individual systems. Finally the viability of solutions used by Zoom, Teams, Google Meet, Jitsi and Vooler are evaluated with the help of an interview based case study. The results of the study favour Vooler when it is evaluated for elderly people use, when considering basic use and accessibility.
Keywords: user experience, user experience evaluation, usability, usability evaluation, accessibility, elderly, video call